ANALISIS PERBANDINGAN PENDAPATAN PENGGILINGAN PADI STATIS DAN PENGGILINGAN PADI MOBILE DI KECAMATAN MANYAK PAYED KABUPATEN ACEH TAMIANG - Nafisatul Ula; Fiddini Alham; Faoeza Hafiz Saragih (Jurnal Cakrawala Ilmiah, 2024)
This study aims to analyze the comparison of income from static rice milling and mobile rice milling in manyak payed sub-districts, aceh tamiang district. the method of determining the sample using a sampling technique, namely quota sampling as many as 20 respondents, static rice milling as many as 10 respondents and mobile rice milling as many as 10 respondents. The data collected in this study are primary data and secondary data. Data analysis methods used in this study are cost analysis, revenue analysis, income analysis and also use the Mann-Whitney test.The results showed that the average income earned by the static rice milling business was Rp.269.307.185 per month, while the average income earned by mobile rice milling business is Rp. 280.420.417 per month. Data processing is carried out using SPSS version 16 computer software. The results of the calculation of the difference in the average income of a static (fixed) rice milling business and a mobile (mobile) rice milling business, with an Asymp.Sig. (2-tailed) value or a P Value of 0.545 greater than 0.05 (0.545>0.05). then these results indicate that H0 is accepted, meaning that there is no difference in income from static (fixed) and mobile (mobile) rice milling operations where the P-value (sig.2-tailed) obtained is greater than 0.05 (>0 ,05).